A TRIGONOMETRIA ESTUDADA ATRAVÉS DE SOFTWARES LIVRES - Roncaglio, Viviane; Uecker, Taciana; Spilimbergo, Angela P. G.; Piva, Cláudia; Dorneles, Lecir D.; Souza, Marco A. d. (Salão do Conhecimento, 2013)
Resumo